A comparative Study on Synthesis, Characterization and Antibacterial Activity of Green vis-a-vis Chemically Synthesized Silver Nanoparticles - Sharma, Arun Kumar; Rana, Kiran; Shrestha, Sita; Oli, Hari Bhakta; Bhattarai, Deval Prasad (Amrit Research Journal, 2022)
Green synthesis of silver nanoparticles is of great importance in the field of nanoscience and nanotechnology. Various phytochemical constituents present in whole or parts of plants can act as reducing, capping and stabilizing agents in the synthesis of silver nanoparticle (AgNPs) by green method. In this work, AgNPs have been successfully synthesized in the laboratory by chemical reduction and green method. NaBH4 was used as a reducing agent in chemical reduction method whereas Zingiber officinale leaf extract was used as reducing and capping agent in green method. The properties of as synthesized AgNPs by both green and chemical methods have been examined by UV-Vis spectroscopy, XRD and FTIR method. Besides these, biological activities of as synthesized AgNPs were tested against Bacillus subtilis and Escherichia coli which exhibited remarkable antimicrobial activities in green method. Based on the result, it is found that AgNPs synthesized from ginger plant (Zingiber officinale) leaf extract exhibited significant antimicrobial effect than that by chemically synthesized AgNPs.